Consequences of habitat fragmentation on the reproductive success of two Tillandsia species with contrasting life history strategies. Issue 4 (19th June 2018) - Sáyago, Roberto; Quesada, Mauricio; Aguilar, Ramiro; Ashworth, Lorena; Lopezaraiza-Mikel, Martha; Martén-Rodríguez, Silvana
Abstract: Fragmentation of natural habitats generally has negative effects on the reproductive success of many plant species; however, little is known about epiphytic plants. We assessed the impact of forest fragmentation on plant–pollinator interactions and female reproductive success in two epiphytic Tillandsia species with contrasting life history strategies (polycarpic and monocarpic) in Chamela, Jalisco, Mexico, over three consecutive years. Hummingbirds were the major pollinators of both species and pollinator visitation rates were similar between habitat conditions. In contrast, the composition and frequency of floral visitors significantly varied between habitat conditions in polycarpic and self-incompatible T. intermedia but not in monocarpic self-compatible T. makoyana . There were no differences between continuous and fragmented habitats in fruit set in either species, but T. makoyana had a lower seed set in fragmented than in continuous forests. In contrast, T. intermedia had similar seed set in both forest conditions. These results indicate that pollinators were effective under both fragmented and continuous habitats, possibly because the major pollinators are hummingbird species capable of moving across open spaces and human-modified habitats. However, the lower seed set of T. makoyana under fragmented conditions suggests that the amount and quality of pollen deposited onto stigmas may differ between habitat conditions. Alternatively, changes in resource availability may also cause reductions in seed production in fragmented habitats. This study adds to the limited information on the effects of habitat fragmentation on the reproductive success of epiphytic plants, showing that even related congeneric species may exhibit different responses to human disturbance. Plant reproductive systems, along with changes in pollinator communities associated with habitat fragmentation, may have yet undocumented consequences on gene flow, levels of inbreeding and progeny quality of dry forest tillandsias. Abstract : This study assessed the impact of habitat fragmentation on plant–pollinator interactions and reproductive success of two epiphytic Mexican Tillandsia species over 3 years. Pollinator assemblages changed in species composition between fragmented and continuous habitats for T. intermedia, but hummingbirds—the most important pollinators of both Tillandsia species—were effective under both habitat conditions, reflecting their ability to move across human-modified landscapes. Tillandsia makoyana had a lower seed set under fragmented conditions, suggesting that differences in pollination quality between habitat conditions may have undocumented consequences on the quality progeny of these dry forest Tillandsia species.